Determinants of Sharia Life Insurance Productivity in Indonesia - Puji Sucia Sukmaningrum; Achsania Hendratmi; Syadiyah binti Abdul Shukor; Mutiara Ramadhani Putri; Rosin Putra Gusti (Elsevier, 2024)
Indexed by Scopus